An in vitro gastrulation model recapitulates the morphogenetic impact of pharmacological inhibitors of developmental signaling pathways. Issue 12 (9th October 2015) - Li, Aileen S. W.; Marikawa, Yusuke
SUMMARY: Certain chemical agents act as teratogens, causing birth defects and fetal deaths when pregnant women are exposed to them. The establishment of in vitro models that recapitulate crucial embryonic events is therefore vital to facilitate screening of potential teratogens. Previously, we created a three‐dimensional culture method for mouse P19C5 embryonal carcinoma stem cells that, when cultured as embryoid bodies, display elongation morphogenesis resembling gastrulation, which is the critical event resulting in the germ layers and major body axes. Determination of how well this in vitro morphogenesis represents in vivo gastrulation is essential to assess its applicability as well as to identify limitations of the model for detecting teratogenic agents. Here, we investigated the morphological and molecular characteristics of P19C5 morphogenesis using pharmacological agents that are known to cause abnormal patterning in the embryo in vivo by inhibiting major developmental signaling—e.g., involving Wnt, Nodal, Bone morphogenic protein (Bmp), Fibroblast growth factor (Fgf), Retinoic acid, Notch, and Hedgehog pathways. Inhibitors of Wnt, Nodal, Bmp, Fgf, and Retinoic acid signaling caused distinct changes in P19C5 morphogenesis that were quantifiable using morphometric parameters. These five inhibitors, plus the Notch inhibitor, also altered temporal expression profiles of developmental regulator genes in a manner consistent with the in vivo roles of the corresponding signaling pathways. In contrast, the Hedgehog inhibitor did not have any impact on the process, suggesting an absence of active Hedgehog signaling in these embryoid bodies. These results indicate that the P19C5 in vitro gastrulation model is a promising tool to screen for teratogenic agents that interfere with many of the key developmental signals. Mol. Reprod. Dev. 82: 1015–1036, 2015. © 2015 Wiley Periodicals, Inc .